EXAMINING TRANSLATION PROBLEMS IN INDONESIAN TOURISM BROCHURES: A CASE FROM GORONTALO - Novriyanto Napu; Usman Pakaya (Premise: Journal of English Education and Applied Linguistics, 2021)
The purpose of this study is to examine the English translations of brochures published by the Tourist Board of Gorontalo Province Government in Indonesia. This quantitative study looked at tourism brochures, both in Indonesian and English, as the source of data. The data were analyzed by considering the frequency and percentage to assess the problems of the English translation used as promotional material. The results reveal that the most frequent problems were syntactic problems (61.54%), followed by semantic problems (26.37%) and miscellaneous problems (12.09%) respectively. This study is expected to contribute to the form of feedback and implications regarding the level of problems and effectiveness of the promotional material in English for future improvement. The results of this study can also be used to develop a model for the use of effective and persuasive English to improve the quality of tourism promotion material by the aforementioned party so that there will be an increased number of interest in foreign tourists visiting Gorontalo in the future. The implication in language learning especially in translator training is also considered.